Bumblebee resource dynamics : a review of foraging and nesting in the agricultural landscape - Douhan Sundahl, Anna (SLU/Dept. of Ecology, 2020)
90 % of all plants on earth either benefits or entirely depends on pollination. There are pollinators among families of bees (Apidea), butterflies (Lepidoptera) and birds (Aves). Bees of genus Bombus spp., bumblebees, are especially important and provide pollination service for 80 % of the crops of Europe and many wild plant species. The bumblebee community both rise and fall within the same year with few exceptions. Only the newborn queen survives to the next year to form a new community. Since the intensification of agriculture many bumblebees species have been declining in numbers.